(untitled) (Bangladesh Journal of Medical Science, 2013)
Fifty different cases of post-operative abdominal wound infection and per-operative contamination related to wound infection were analized from swabs/pus. Most common organism isolated was Escherichia coli and next was Staplylococcus sp., indicate most wound infection after abdominal surgery is caused by endogenous organism of gastrointestinal tract. DOI: http://dx.doi.org/10.3329/bjms.v12i1.10982 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.86-90